Care and respect: mothering and relatedness in multigenerational prison settings - Cunha, Manuela Ivone P. da (2013)
Drawing on fieldwork conducted in different periods in Portuguese carceral settings, we focus on variable aspects of motherhood and forms of relatedness as they emerge in different imprisonment situations. Aspects approached include: the relationship of incarcerated mothers with their offspring behind and beyond bars (children and/or adults, since imprisonment situations may comprehend three generations of co-confined relatives); motherhood in prisoners’ social identity and in carceral sociality; experiences of mothering in prison and mothers’ experiences of imprisonment; notions of care and care responsibilities; respect, reciprocity and moral obligation in relation to parenthood.